IMPLEMENTASI KEBIJAKAN BADAN LAYANAN UMUM DAERAH TERHADAP EFEKTIVITAS PELAYANAN PADA INSTALASI RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH SEKARWANGI - Arie Melani Purbasari (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2022)
Sekarwangi Regional General Hospital, Sukabumi Regency changed its status from SKPD/OPD to Regional Public Service Agency for Sekarwangi Hospital since January 1, 2010, The implementation of the policy is expected to improve health services. The backgroundof the implementation of BLUD policies is that the division of labor in services is not yet optimal, the details of costs in the Budget Business Plan are not yet complete, RSUD employees do not understand the pattern of professional BLUD management. The work orientation of employees does not reflect the pattern of BLUD management. Therefore, this study describes the effect of BLUD policy implementation on the effectiveness of services in outpatient installations. This study took a sample of 98 people with descriptive and quantitative/correlation data analysis techniques. Correlation analysis of variable (X) with variable (Y) using SPSS 13 For Windows. The two research variables are strongly correlated, the analysis above proves that the significance figure can be known, the total correlation coefficient is 0.581 (medium/sufficient level). The results of the study stated: There is a positive and significant effect between the implementation of policies regarding regional public service agencies on the effectiveness of services in outpatient installations at Sekarwangi Hospital, Sukabumi Regency